Penerapan Pembelajaran Berdiferensiasi Konten, Proses, dan Produk untuk Meningkatkan Hasil Belajar Siswa Sekolah Menengah Pertama - Muhammad Agung; Ratna Dewi; Arfiah Ainun Salsabila (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2024)
This study examines English learning outcomes through the use of differentiate appropriate practice with Project-Based Learning among students of class IX (9b2) SMP Unismuh Makassar. A classroom action research with two cycles was conducted. The researcher collected data by conducting assessment (summative and formative) and classroom observation by using evaluation tests, learning style questionnaire, and observation sheets. The findings show that there is an improvement in learning outcomes from cycle 1 (average score of cognitive domain is 69.09 and psychomotor is 70) and cycle 2 (average score of cognitive domain is 89.32 and psychomotor is 74.2), while the result of the affective domain by using the attitude journal shows that the frequency of negative behavior reduced from cycle 1 to cycle 2. These findings indicate that the implementation of the teaching stratagy improves the students’ learning outcomes of the cognitive, psychomotor, and affective domains. The result can be used by junior high school teacher as a reference by implementing differentiate appropriate practice that highlights differentiate content addressed learning style, process addressed readiness, and product addressed cultures.